2016
DOI: 10.1039/c5sm02022k
|View full text |Cite
|
Sign up to set email alerts
|

The twisted tauopathies: surface interactions of helically patterned filaments seen in alzheimer's disease and elsewhere

Abstract: This paper broadly examines the dynamics of helically patterned filaments interacting with a surface and focuses on the surface interaction of amyloid fibrils formed by tau protein. Two structures are addressed in detail: cylindrical filaments with periodic thinning (CF-PT) and paired helical filaments (PHFs). PHFs are observed in neural tissue affected by Alzheimer’s disease and may aggregate to form the pathological neurofibrillary tangles associated with the illness. Work using electron microscopy has demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…22 Also, the surface interaction of helical filaments from twisted tauopathies observed in the research of Alzheimer's disease recently attracted significant attention facilitated by the progress in the scanning transmission electron microscopy. 23,24 In addition, the similarity of the cross section of twisting carbon nanotube yarns 25 and the cross section of human muscle fibers also indicates the feasibility of filament twisting during muscle contraction. Some theoretical models of the shape dynamics of helical filaments bound to a surface are available.…”
Section: ■ Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…22 Also, the surface interaction of helical filaments from twisted tauopathies observed in the research of Alzheimer's disease recently attracted significant attention facilitated by the progress in the scanning transmission electron microscopy. 23,24 In addition, the similarity of the cross section of twisting carbon nanotube yarns 25 and the cross section of human muscle fibers also indicates the feasibility of filament twisting during muscle contraction. Some theoretical models of the shape dynamics of helical filaments bound to a surface are available.…”
Section: ■ Introductionmentioning
confidence: 89%
“…Some theoretical models of the shape dynamics of helical filaments bound to a surface are available. 23,26 In distinction from those works, the model developed here can predict the dynamic configurations of curved filaments in any shape, rather than only an ordinary helix.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Within the cell, MreB can be either a helix or a ring. [3][4][5][6][7][8][9][10][26][27][28][29][30][31] It was found that MreB filaments have a persistence length 5 to 10 times larger than the bacterial cell size. 3,13 Consequently, the shape of the cell provides a strong constraint on the MreB filament.…”
Section: Introductionmentioning
confidence: 99%